Women Oppression’s Portrayal in Taylor Jenkin Reid’s The Seven Husbands of Evelyn Hugo - Damayanti, Alfina Putri (English Literature Study Program, 2023)
In this modern world, the phenomenon of women oppression has become more prevalent in society. Oppression against women has been embedded for generations and can really happen under any circumstances. However, this phenomenon is not only actualized in real life but is also portrayed in Taylor Jenkins Reid’s work entitled The Seven Husbands of Evelyn Hugo. The aims of this study are divided into two categories: first, to identify forms of oppression experienced by women characters, Monique Grant and Evelyn Hugo, and second, to describe women characters' struggle against oppression in the novel. The approach used in this study is the sociology of literature since the novel brings up social life issues such as inequalities based on class, race, gender, and other aspects, which these issues might be examined through the perspective of liberal feminism. Additionally, the researcher uses the ‘Five Faces of Oppression’ theory by Irish Marion Young to identify forms of oppression. The results of this study revealed that Monique and Evelyn experienced oppression due to their gender and racial background. Monique was marginalized in the workplace, whereas Evelyn was subjected to the five faces of oppression mentioned by Young, both in the private and public spheres. However, despite the oppression that Monique and Evelyn experienced, they were struggling for their freedom and rights in order to take control of their own lives and careers. Their struggles are intertwined with liberal feminism, a theory that advocates for changing laws, policies, and institutions in order to eliminate gender equality in all aspects of life.